1991
DOI: 10.1021/ic00011a004
|View full text |Cite
|
Sign up to set email alerts
|

Site-selective spectroscopy of luminescent square-planar platinum(II) complexes

Abstract: We report on the site selective luminescence spectroscopy of wazu-Pt(H)Cl(PEt3)2, franj-Pt(C^CH)2(PEt3)2, and trans-Pt-(CssCPh)2(PEt3)2. All complexes give intense 77 K emission spectra and have site selective differences in their luminescence properties in a variety of rigid glasses. Depending on precise structure, site sensitivity can be very small to extremely large. The variations in behavior are explained on the basis of the charge-transfer character of the excited state, the environmental volume sampled,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
56
0
1

Year Published

2001
2001
2007
2007

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(65 citation statements)
references
References 9 publications
(11 reference statements)
8
56
0
1
Order By: Relevance
“…A similar behavior is observed in frozen CH 2 Cl 2 glass (77 K) and, to illustrate this, the spectra obtained by increasing the excitation wavelength from 380 to 410 nm are shown in Figure 7. This behavior suggests the existence of ground-state heterogeneity [121] or, more likely, the presence of at least two closely lying emissive states. The emission lifetime data (see Table 6) indicate spin-forbidden processes showing lifetime values that increase upon cooling, consistent with a reduction in the nonradiative decay rates, as expected.…”
Section: Excitation Of Solid Hexanuclear Complex [{Ptcu 2 a C H T U Nmentioning
confidence: 93%
See 1 more Smart Citation
“…A similar behavior is observed in frozen CH 2 Cl 2 glass (77 K) and, to illustrate this, the spectra obtained by increasing the excitation wavelength from 380 to 410 nm are shown in Figure 7. This behavior suggests the existence of ground-state heterogeneity [121] or, more likely, the presence of at least two closely lying emissive states. The emission lifetime data (see Table 6) indicate spin-forbidden processes showing lifetime values that increase upon cooling, consistent with a reduction in the nonradiative decay rates, as expected.…”
Section: Excitation Of Solid Hexanuclear Complex [{Ptcu 2 a C H T U Nmentioning
confidence: 93%
“…On the basis of previous assignments [5,10,[120][121][122][123][124] and theoretical studies, [120,[125][126][127] the lowenergy shoulder that is observed at 315 nm in CH 2 Cl 2 and slightly blue-shifted in NCMe (310 nm), is attributed tentatively to an admixture of p!p*A C H T U N G T R E N N U N G (C CPh) IL/dp(Pt)!p*A C H T U N G T R E N N U N G (C CPh) MLCT. [128] In agreement with this assignment, the band is notably blue-shifted in relation to that seen in the homoleptic derivative (NBu 4 ) 2 [PtA C H T U N G T R E N N U N G (CCPh) 4 ] (347 nm) [127] in which its dianionic nature presumably increases the energy of the HOMO (dp(Pt)/pA C H T U N G T R E N N U N G (CC)), [128] .…”
mentioning
confidence: 92%
“…[17,18] The photoluminescence of [trans-Pt(CϵCR) 2 ](PEt 3 ) 2 , where R ϭ H or phenyl, in the solid state and frozen glass solution at 77 K was investigated by Demas and co-workers. [19] The emission was assigned as arising from a charge transfer excited state involving Pt d z 2 and acetylide π* orbitals. Yam and co-workers reported the luminescence of branched alkynylplatinum() complexes containing the [PtCl(CϵCC 6 H 4 CϵC)(PEt 3 ) 2 ] moiety, and suggested that the emission originates from a mixed π Ǟ π* (CϵCR) intraligand (IL)/d z(Pt) Ǟ π* (CϵCR) MLCT triplet state with predominantly IL character.…”
Section: +mentioning
confidence: 99%
“…[52][53][54] Many of these complexes, particularly those containing Tl I , have been shown to display luminescent properties, which have invariably been attributed to intermetallic interactions; however, a number of Pt II,0 ÀTl I complexes with strong Pt-Tl interactions do not exhibit any detectable emission. [55,56] In the past two decades, much has been discovered about the photoluminescence behavior of alkynylplatinum(ii) complexes, [57][58][59][60][61][62] but, in comparison, relatively little is understood about the emissive properties of heteropolynuclear platinum systems containing alkynyl bridging ligands. [63][64][65][66] Recent studies by us [67][68][69][70] and others [63,66] 8 ] by sandwiching naked Tl I centers through Tl I -alkyne interactions, [71] thus indicating that in these systems the Tl I centers have a stronger preference for the electron-rich alkynyl entities than for the basic Pt II center.…”
Section: Introductionmentioning
confidence: 99%